2014
DOI: 10.3892/ol.2014.2813
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of microRNA-92a in colorectal adenocarcinoma and its precancerous lesions: Co-utilization of in situ hybridization and spectral imaging

Abstract: The expression level of microRNA (miR)-92a has been proven to increase during the development of colorectal adenocarcinoma (CA) and has been verified at the cellular, plasma and fecal levels by various quantitative methods. However, a method to quantitate the expression level using tissue sections has not been established. To do this, in situ hybridization (ISH) and multispectral imaging microscopy (MSI) were introduced to quantitate miR-92a expression on the microscopic level. ISH of miR-92a was first perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…We observed that miR-92a, a well-characterized oncomiR in colorectal cancer (9094) was upregulated in stem cells, while miR-124 a tumor suppressor in colorectal cancer was downregulated in stem cells as compared to differentiated cells (9597). Interestingly, other members of miR-17-92, e.g., miR-18a and miR-20b, were also upregulated in AOM-Lgr5 negative cells.…”
Section: Discussionmentioning
confidence: 89%
“…We observed that miR-92a, a well-characterized oncomiR in colorectal cancer (9094) was upregulated in stem cells, while miR-124 a tumor suppressor in colorectal cancer was downregulated in stem cells as compared to differentiated cells (9597). Interestingly, other members of miR-17-92, e.g., miR-18a and miR-20b, were also upregulated in AOM-Lgr5 negative cells.…”
Section: Discussionmentioning
confidence: 89%
“…MiR-92a expression levels were scored using the following four-tier scoring system according to the staining intensity: 0 = negative, 1 = weak positive, 2 = moderate and 3 = strong positive. Expression levels were considered as negative, final score ≤ 0.5 or positive 0.5 < final score ≤ 3 [ 16 ]. Cytoplasmic miR-10b staining was categorized as follows: low-expression, < 20 % of cells stained; high-expression, ≥ 20 % of cells stained [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the studies of colorectal cancer, hepatocellular carcinoma, pancreatic cancer, cervical cancer and osteosarcoma, miR-92a was reported to exert oncogenic influence on cancer progression. [9][10][11][12][13][14] However, our data revealed a tumor suppressive role of miR-92a in PCa using both gain-and loss-of function assays. These indicate that the functional influence of miR-92a in human cancers differs in different types of human cancers.…”
Section: Discussionmentioning
confidence: 94%
“… 6 They were proposed as the promising biomarkers and therapeutic targets of human cancers including PCa. 7 , 8 Recent studies reported that miR-92a played critical roles in the progression of colorectal cancer, 9 , 10 hepatocellular carcinoma, 11 pancreatic cancer, 12 cervical cancer 13 and osteosarcoma. 14 It was found to promote the proliferation, metastasis, and metabolism of cancer cells and its expression levels in cancer tissues was correlated with the clinical prognosis of patients.…”
Section: Introductionmentioning
confidence: 99%